2022
DOI: 10.1007/s10900-022-01090-8
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Susceptibility and Severity of COVID-19 on Prevention Practices, Early in the Pandemic in the State of Florida

Abstract: Early in the pandemic and prior to the development of the COVID-19 vaccine, prevention measures were promoted to help inhibit the spread of the virus. To optimize adherence to prevention practices, it's important to understand factors that may influence adherence. A study was conducted in the month of April, 2020, to explore the influence of perceptions of COVID-19 on prevention practices. The sample included members of a public social-media group focused on providing updates and information on COVID-19. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
(40 reference statements)
3
8
0
1
Order By: Relevance
“…Several studies have shown that perceptions toward COVID-19 vaccination and perceived susceptibility to contracting the virus can predict whether an individual will engage in protective health behaviors. 37 - 39 We found that most patients with CKD were concerned with getting infected with COVID-19. This finding is consistent with both quantitative and qualitative data from studies that have shown that people living with CKD, including patients on dialysis and kidney transplant recipients, are quite concerned or feel vulnerable about contracting COVID-19.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have shown that perceptions toward COVID-19 vaccination and perceived susceptibility to contracting the virus can predict whether an individual will engage in protective health behaviors. 37 - 39 We found that most patients with CKD were concerned with getting infected with COVID-19. This finding is consistent with both quantitative and qualitative data from studies that have shown that people living with CKD, including patients on dialysis and kidney transplant recipients, are quite concerned or feel vulnerable about contracting COVID-19.…”
Section: Discussionmentioning
confidence: 92%
“…Perceived severity encompasses evaluations of the health consequences of a disease as well as its broader social consequences. PSC has been widely studied during the COVID‐19 pandemic (Das & Kumar, 2022; DeDonno et al., 2022; Deng et al., 2020; Li et al., 2020). A high perception of disease severity engenders proactive health‐protective behaviors (Li et al., 2020; Weinstein, 2000).…”
Section: Theoretical Lens and Hypothesesmentioning
confidence: 99%
“…Various theoretical models have been proposed to explain health behaviors. The Health Belief Model considers vulnerability, benefits, and barriers [19][20][21], which together with self-efficacy help explain the use of COVID-19 preventive measures [22][23][24][25][26]. Expectations also play a key role in maintaining a healthy behavior, and continuing the use of face masks may depend on the expected benefits of the vaccine; if the result does not occur in the way it was anticipated, the behavior may be abandoned or replaced [27].…”
Section: Introductionmentioning
confidence: 99%